Neuropsychological Impairment in Children With Class 1 Congenital Heart Disease. Issue 5 (October 2019) - Venchiarutti, Martina; Vergine, Michela; Zilli, Tiziana; Sommariva, Giulia; Gortan, Anna Jolanda; Crescentini, Cristiano; Urgesi, Cosimo; Fabbro, Franco; Cogo, Paola
Children with congenital heart disease (CHD) are at increased risk of neuropsychological impairments, but few studies are available on the nonlinguistic neuropsychological abilities of children with CHD. We conducted neuropsychological evaluations using the NEPSY II on a cohort of 17 school-age Italian children with diagnoses of Class 1 CHD, no genetic or chromosomal abnormalities, and normal intelligence scores, and we compared them with 34 matched controls. Children with CHD in this study had undergone at least one cardiac surgery with cardiopulmonary bypass support. We found that children with CHD scored significantly lower than their matched controls on memory and learning domain tasks, and they displayed subtle attention/executive dysfunctions and deficits in sensorimotor skills.